(untitled) (Research, Society and Development, 2022)
We evaluated the changes in fishing dynamics and in social, economic, political-institutional and ecological aspects, in two communities of the reservoir Santo Antônio Hydroelectric: District Jaci Paraná and Vila Nova do Teotônio, Rondônia, Brazil. The fishing dynamics and the Development Index Fishermen of Middle Madeira (IDPM) were obtained and compared between the periods: 2007/2009 and 2017/2019. We observed: reduction in the capture and contribution of communities in the Porto Velho market; variations in catch composition, decrease of some species; and decrease in the average monthly income of fishermen. The IDPM of the localities decreased in the POSR and below the ideal of development, influenced by the low performance of the ecological and fisheries indicators. Both locations suffered with the changes, the few fishermen who persisted in the activity, demonstrate adaptation strategies to the new scenery, with variations between locations.